Protocolo De Diagnóstico De Tremátodos Paramphistomum Spp y Fasciola Hepática En Bovinos (2021)
Parasitosis in cattle caused by trematodes such as Fasciola hepatica and Paramphistomum spp generate significant economic losses, this happens when environmental conditions are ideal for the survival of intermediate hosts, which allow the parasites to complete their life cycle and then affect to its definitive hosts, among which are sheep, cattle, goats, pigs, horses, other herbivorous animals and accidentally to man, this occurs especially in humid areas of temperate climate regions. The favorite organs of the Fasciola hepatica trematode are the bile ducts of the liver and gallbladder, the favorite organ of Paramphistomum adults is the rumen and that of the immature stages the small intestine (Román, 2016). Massive infection usually causes the death of affected animals; In addition, there are considerable economic losses due to the decomposition of the parasitized livers and the decrease in the production of meat and milk (Bravo, 2007). In this work, a protocol for the diagnosis of trematode parasites is proposed, which goes from ante-mortem diagnosis on the farm (breeding, raising and production of cattle), to the processing plant, where the affected animals will be diagnosed post-mortem . This in order to carry out an orderly investigation and to facilitate the search and consolidation of information on parasites to professionals and entities interested in their diagnosis.